2005
DOI: 10.1002/ejoc.200400804
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Absolute Configuration of Hyperaspine, an Alkaloid of the Ladybird Hyperaspis campestris

Abstract: Hyperaspine (1a), isolated from the European Coccinellidae Hyperaspis campestris, isthe first representative of a new type of ladybird alkaloids having a 3‐oxaquinolizidine skeleton. A new total synthesis of (±)‐hyperaspine starting from protected piperidin‐4‐one has been achieved. The absolute configuration of the natural alkaloid was unequivocally established to be 3S,4aS,6R,8S by HPLC analyses on a chiral column. (© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2005)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Conjugate addition of a dialkylcuprate, prepared from pentylmagnesium bromide and CuI, to 7 provided nearly complete (>96% de) facial selectivity affording a 92% yield of piperidone 8 . This stereochemical outcome was anticipated on the basis of stereoelectronic arguments and literature precedent. ,6b Ma and Zhu reported that bicyclic ketone 8 is reduced with LS-Selectride to give alcohol 9b , which was esterified with inversion via the Mitsunobu reaction to provide hyperaspine 2b. Braekman and co-workers reduced racemic 8 with NaBH 4 to give a 1:1 mixture of the two inseparable epimeric alcohols .…”
mentioning
confidence: 77%
See 3 more Smart Citations
“…Conjugate addition of a dialkylcuprate, prepared from pentylmagnesium bromide and CuI, to 7 provided nearly complete (>96% de) facial selectivity affording a 92% yield of piperidone 8 . This stereochemical outcome was anticipated on the basis of stereoelectronic arguments and literature precedent. ,6b Ma and Zhu reported that bicyclic ketone 8 is reduced with LS-Selectride to give alcohol 9b , which was esterified with inversion via the Mitsunobu reaction to provide hyperaspine 2b. Braekman and co-workers reduced racemic 8 with NaBH 4 to give a 1:1 mixture of the two inseparable epimeric alcohols .…”
mentioning
confidence: 77%
“…This stereochemical outcome was anticipated on the basis of stereoelectronic arguments and literature precedent. ,6b Ma and Zhu reported that bicyclic ketone 8 is reduced with LS-Selectride to give alcohol 9b , which was esterified with inversion via the Mitsunobu reaction to provide hyperaspine 2b. Braekman and co-workers reduced racemic 8 with NaBH 4 to give a 1:1 mixture of the two inseparable epimeric alcohols . Since a stereoselective reduction of (+)- 8 to the aminal alcohol 9a is advantagous, we investigated the use of a dissolving metal reduction.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…Other natural product syntheses have used the anodic oxidation approach, often as the first step in a synthesis campaign to functionalise a pyrrolidine or piperidine carbamate [ 86 – 87 ].…”
Section: Reviewmentioning
confidence: 99%